2016
DOI: 10.5018/economics-ejournal.ja.2016-30
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Competitiveness on Trade Balance: The Case of Southern Europe

Abstract: According to conventional wisdom, "peripheral" Southern European members of the euro area (Greece, Italy, Portugal and Spain) suffer from a problem of competitiveness. Since their membership of the euro area renders devaluation impossible, adjustment should come through decreasing wages and prices in these countries, which, by improving the trade balance, should lead to a recovery of previous levels of employment and growth. In this paper, the authors estimate trade balance equations for the Southern European … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
4
0
2
Order By: Relevance
“…Overall, these results suggest that financial markets are developed enough, at least in advanced countries, so that exchange rate volatility has not hindered the evolution of exports. In addition, when coupled with the results in Bajo-Rubio et al (2016), boosting world demand appears as the main factor that might encourage a recovery of European trade throughout the current crisis.…”
Section: Discussionmentioning
confidence: 98%
“…Overall, these results suggest that financial markets are developed enough, at least in advanced countries, so that exchange rate volatility has not hindered the evolution of exports. In addition, when coupled with the results in Bajo-Rubio et al (2016), boosting world demand appears as the main factor that might encourage a recovery of European trade throughout the current crisis.…”
Section: Discussionmentioning
confidence: 98%
“…According to Bajo-Rubio and Esteve (2016), there is no obvious empirical relationship between the exchange rate and the trade balance among Southern European countries that are members of the Eurozone (Greece, Italy, Portugal, and Spain). Spain and Italy have done well, despite their economies' lower productivity and their incapacity to engage in the monetary and exchange rate sectors, because their major exports originate from large domestic enterprises (Bajo-Rubio & Esteve, 2016). Shawa and Shen (2013) found that the factors influencing Tanzania's trade balance are often not included in empirical research.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This leaves the issue of the trade balance effect of currency depreciation empirical. Though appreciation or depreciation of exchange rate does not guarantee the loss or gain of competitiveness, movements of domestic wages and prices (the so-called internal interventions) do matter (Bajo-Rubio et al, 2016); many countries around the world operating under both fixed and flexible exchange rate regimes have undervalued their currencies to improve their trade balances since the early 1970s. Baldwin and Krugman (1989) and Clark et al (1994) explain how currency overvaluation can be the cause of persistent loss of trade competitiveness with the notion of 'hysteresis effect' -an effect that persists when its causes are removed.…”
Section: Theoretical Literaturementioning
confidence: 99%